2020
DOI: 10.1038/s41598-020-66305-1
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory control of human gait following simulated slip exposure

Abstract: Rob den otter & claudine J. c. Lamoth A cautious gait (cG), marked by wider and shorter steps, is typically employed to mitigate expected perturbations proactively. However, it is not well understood if and how cG is informed by the task requirements. therefore, we assessed how cG is adjusted to these requirements. three groups of ten healthy young adults were exposed to a single uninterrupted protocol of treadmill walking that consisted of three distinct phases. Spatiotemporal step characteristics and margins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…When a perturbation occurs, the cerebral cortex instinctively responds by adopting more cautious gait to position the body for stability [ 41 ]. Generally such gait alterations are referred to as gait placement strategies [ 17 , 18 ].These deliberate modifications protect the dynamic stability and can lessen the requirement for time-critical, reactive control [ 9 , 42 ]. As such, it is frequently employed by older adults [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When a perturbation occurs, the cerebral cortex instinctively responds by adopting more cautious gait to position the body for stability [ 41 ]. Generally such gait alterations are referred to as gait placement strategies [ 17 , 18 ].These deliberate modifications protect the dynamic stability and can lessen the requirement for time-critical, reactive control [ 9 , 42 ]. As such, it is frequently employed by older adults [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gait pattern alterations are typically characterized and quantified in terms of spatiotemporal parameters [ 44 ]. To proactively reduce anticipated disturbances, wider and shorter steps are regularly applied, which likewise works for unanticipated ones [ 42 ].Wider steps taken voluntarily help improve immediate lateral stability [ 45 ], and shorter step length can lead to an increase in the medio-lateral and backward MoS against anterior–posterior slip [ 46 , 47 ]. These observable stepping strategies are an important contribution to fall prevention [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been shown that after perturbation exposure, healthy adults adopt a more cautious gait i.e. with shorter, wider, and slower steps as a means to enhance their dynamic stability to prevent potential future perturbations [ 10 , 22 ]. It is possible that our participants used a similar strategy when walking after initial slip exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, in the unperturbed (recovery) limb, the hip and knee extend to bring the leg that is entering the swing phase rapidly to the ground to increase the base of support (BOS) [ 16 ]. After slip exposure, individuals walk with a “cautious gait” strategy where step time and width are increased, and step length is reduced [ 20 , 22 , 23 ]. This is accompanied by a shift in the dynamical state (position and velocity) of their COM anteriorly and away from the mediolateral edges of their base of support at heel-strike [ 10 , 18 , 20 ].…”
Section: Introductionmentioning
confidence: 99%